Broadband RCS Reduction of Antenna with AMC Using Gradually Concentric Ring Arrangement - Fuwei Wang; Yuhui Ren; Ke Li (International Journal of Antennas and Propagation)
This paper proposes a new method to the broadband RCS reduction with the artificial magnetic conductor (AMC) surfaces. The AMC surfaces can introduce a zero-degree reflection phase shift to incident waves. The phase difference between the antenna and AMC structures is 180°. Therefore, the AMC structures can be used to achieve RCS reduction. However, the bandwidth of zero-degree reflection phase of AMC structures is very narrow. In light of this, a novel gradually concentric ring arrangement AMC (GCRA-AMC) which can be applied to achieve the broadband RCS reduction is presented. The simulated and measured results show that the radiation performance of antennas is preserved when the GCRA-AMC is used. The RCS of the antenna with GCRA-AMC has been considerably reduced in a broad frequency band. The largest RCS reduction is more than 17 dB.